2020
DOI: 10.3390/microorganisms8101587
|View full text |Cite|
|
Sign up to set email alerts
|

Gut Microbiota and Immune System Interactions

Abstract: Dynamic interactions between gut microbiota and a host’s innate and adaptive immune systems play key roles in maintaining intestinal homeostasis and inhibiting inflammation. The gut microbiota metabolizes proteins and complex carbohydrates, synthesize vitamins, and produce an enormous number of metabolic products that can mediate cross-talk between gut epithelial and immune cells. As a defense mechanism, gut epithelial cells produce a mucosal barrier to segregate microbiota from host immune cells and reduce in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
291
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 461 publications
(364 citation statements)
references
References 144 publications
0
291
1
5
Order By: Relevance
“…A latest finding was reported that mucosal-associated invariant T (MAIT) cells interact with local microbiota and integrate multiple signals, so it plays an important role in local inflammation ( Ioannidis et al, 2020 ). The microbiome at homeostasis colonized in intestinal mucosa can antagonize pathogenic bacteria, clear endotoxin, and play a role of resistance to external environmental factors ( Seo et al, 2020 ); in turn, the intestinal epithelial cells can also affect the community structure of intestinal mucosal microbiota ( Yoo et al, 2020 ). These researches all explain why intestinal mucosal microbiota in this study is highly susceptible to repeated stress-related diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…A latest finding was reported that mucosal-associated invariant T (MAIT) cells interact with local microbiota and integrate multiple signals, so it plays an important role in local inflammation ( Ioannidis et al, 2020 ). The microbiome at homeostasis colonized in intestinal mucosa can antagonize pathogenic bacteria, clear endotoxin, and play a role of resistance to external environmental factors ( Seo et al, 2020 ); in turn, the intestinal epithelial cells can also affect the community structure of intestinal mucosal microbiota ( Yoo et al, 2020 ). These researches all explain why intestinal mucosal microbiota in this study is highly susceptible to repeated stress-related diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…The diet and metabolic statuses of individuals are key factors affecting the diversity and composition of the microbiome [ 13 , 14 ]. In this way, effective management of the nutritional and metabolic status at the systemic level contribute to promoting a healthy gut microbiome, thereby diminishing the risk of intestinal inflammatory diseases such as ulcerative colitis, inflammatory bowel disease, and cancer [ 15 , 16 , 17 , 18 ]. The microbiota have been demonstrated to influence body weight control by affecting the extraction and absorption of calories, influencing the secretion of anorexigenic hormones (GLP-1, PYY, and leptin), and controlling the intestinal gut barrier [ 19 ].…”
Section: Cancer As a Metabolic Diseasementioning
confidence: 99%
“…Gut microbial communities of children, adults, the elderly, and centenarians have been found to cluster apart from one another other [ 12 , 13 ], suggesting that the gut microbial communities may in fact play different roles throughout the aging process. The development of age-related diseases is often associated with gut dysbiosis, changes in the gut microbiota that negatively impact host health [ 14 , 15 ]. Furthermore, aging is typically associated with decreased diversity and Firmicutes to Bacteroides ratio, as well as an increase in some Proteobacteria, opportunistic species, and pathobionts [ 12 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%